Students’ Perception on Game-Based Learning Using Technology: Kahoot! As a Case Study - Ismail, Ismail; Rusdin, Rusdin; Prayudi, Andi; Taufik, Taufik (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
There have been studies which exploring students’ perception on the use of kahoot!. However, research on investigating students’ opinion on the implementation of kahoot and students’ recommendation for educational stake-holders is uncommon. This study relies on semi-structured interview data from 15 second-year students (10 female and 5 male) enrolling in the Introduction to Linguistics Class in English Education Department of STKIP Yapis Dompu. This study aims to explore the benefits of the use of kahoot, the barriers and students’ recommendation to educational stake-holders for improvement. The data were analysed using thematic analysis adapted from (Braun & Clarke, 2006) which consists of 6 steps. The finding of this paper suggested that the implementation of kahoot in learning process had four benefits: Firstly, Kahoot creates fun and interested learning atmosphere. Secondly, it riggers students’ attention and focus. Thirdly, it facilitates comprehension of material Taught. Lastly, Kahoot! fosters positive competitiveness among students. Additionally; there were two main barriers of using kahoot in this research: firstly, limitations on internet access. Secondly, not enough time to answer. The surprising conclusion of the research was that, all participants had never been exposed to game-based learning platform during their formal school (elementary and high school); they only were only exposed to game-based learning platform at this introduction to linguistics class. Therefore; all participants highly recommended to all lecturers and teachers to game-based learning platform in their teaching. This study relied on game-based learning platform kahoot. Therefore, similar study which explores other game-based learning platforms is highly recommended.